Evaluating the environmental efficiency of the Organization of Islamic Cooperation in achieving climate change goals with an emphasis on Saudi Arabia - Alam, Teg (International Journal of Innovative Research and Scientific Studies, 2025)
Evaluating environmental efficiency is crucial for comprehending how governments meet the climate change objectives outlined in SDG 13. This analysis assesses the ecological efficiency of OIC (Organization of Islamic Cooperation) nations, with a particular emphasis on Saudi Arabia. The study examines the connection between different environmental input and output variables to assess the efficiency with which OIC nations use resources to pursue climate objectives. This study employs Data Envelopment Analysis (DEA) to investigate essential input variables, including land area, agricultural area, agricultural product export value, consumer price index, total population, access to electricity, labor force, human development index (HDI), and final consumption expenditure. The output variables encompass CO₂ emissions, protected areas, forest area, agricultural product import value, crude birth and death rates, population density, total fertility rate, employment in industry, GDP, and water stress levels. The results demonstrate that although certain OIC nations attain environmental efficiency, others face challenges reconciling economic development with their climate obligations. Saudi Arabia has achieved notable progress in broadening its energy portfolio and allocating resources towards renewable technologies. Nonetheless, the significant energy consumption and ongoing economic dependence on fossil fuels pose considerable obstacles. This study offers valuable insights that can assist OIC nations in improving their ecological strategies and contribute significantly to global climate change objectives.